MICROBIOLOGICAL CRITERIA FOR ANTISEPTIC SELECTION IN AUTOINFECTIOUS STOMATITIS THERAPY - Gancho, O.V.; Bublii, T. D.; Moshel, T.M.; Fedorchenko, V.I.; Bolshakova, G.M. (Актуальні проблеми сучасної медицини Вісник Української медичної стоматологічної академії, 2025)
Background. This article presents a microbiological rationale for the selection of antiseptics in the treatment of autoinfectious stomatitis. The efficacy of a hexetidine-based preparation, Happylor, was evaluated in comparison with chlorhexidine bigluconate against reference strains of microorganisms, including Candida albicans ATCC 10231, Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Enterococcus faecalis ATCC 29213, Micrococcus luteus ATCC 4698, and Staphylococcus epidermidis ATCC 14990. These strains were obtained from the State Institution “L.V. Gromashevsky Institute of Epidemiology and Infectious Diseases of the National Academy of Medical Sciences of Ukraine” (Kyiv). Minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) for both antiseptics were determined using a quantitative serial microdilution method in accordance with CLSI guidelines and ISO/TC 212 “Clinical Laboratory Testing and In Vitro Diagnostic Test Systems, 2021”. Results. The findings obtained demonstrated that Happylor, containing hexetidine, exhibits pronounced antibacterial and antifungal properties. Notably, its MIC for Gram-positive cocci was significantly lower (0.4 μg/ml) compared to that of chlorhexidine (25 μg/ml), indicating that the bacteriostatic effect of the hexetidine-containing formulation is 62.5 times greater. Additionally, its fungicidal activity against C. albicans was 8.3 times higher than that of chlorhexidine. Happylor was also found to have a prolonged antimicrobial effect, lasting up to 12 hours, and does not require frequent application. Moreover, it is not associated with systemic side effects. Its mechanism of action is based on the inhibition of microbial growth through competition with thiamine. Conclusion. These findings support the potential of Happylor as an effective alternative to chlorhexidine in the comprehensive treatment of autoinfectious stomatitis, particularly in cases involving mixed bacterial and fungal infections.